1992
DOI: 10.1073/pnas.89.24.12048
|View full text |Cite|
|
Sign up to set email alerts
|

The delta-opioid receptor: isolation of a cDNA by expression cloning and pharmacological characterization.

Abstract: A random primed expression cDNA library was constructed from the RNA of NG 108-15 cells. Pools of plasmid DNA were transfected into COS cells, which were screened for their ability to bind 'H-labeled Tyr-D-Thr-GlyPhe-Leu-Thr, a tritiated agonist for the -opioid receptor. A cDNA was isolated that encodes a 371-amino acid-residue protein presenting all the structural characteristics of receptors that interact with guanine nucleotide-binding proteins. Opioid receptors have long been described as membrane receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
283
0
3

Year Published

1994
1994
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 860 publications
(292 citation statements)
references
References 28 publications
6
283
0
3
Order By: Relevance
“…1A, Ϫ, Ϫ). The size of this protein corresponds to the size previously described for ␦-opioid receptor (19,20). Interestingly, we also observed an additional band of about 120 kDa (Fig.…”
Section: Resultssupporting
confidence: 87%
“…1A, Ϫ, Ϫ). The size of this protein corresponds to the size previously described for ␦-opioid receptor (19,20). Interestingly, we also observed an additional band of about 120 kDa (Fig.…”
Section: Resultssupporting
confidence: 87%
“…cDNA library derived from rat cerebrum poly(A)' RNA was screened by hybridization with a DNA fragment comprising a part of the mouse S-opioid receptor subtype cDNA [4,5]. A novel class of cDNA clones (ROR-C) was isolated and nucleotide sequence analysis revealed an open reading frame of 1,101 nucleotides encoding a sequence of 367 amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…Construction of the Library of Mutants-pcDNA3-hDOR consists of a 1.2-kilobase cDNA EcoRI-XhoI fragment of the ␦-opioid receptor (23) sub-cloned at the EcoRI-XhoI site of pcDNA3 (Invitrogen). Using unique site elimination (USE) mutagenesis (43), pcDNA3-hDOR was mutated to pcDNA3-␦/ 291-300 by replacing 10 amino acids (positions 291-300) of the third extracellular loop of the ␦ receptor with the corresponding amino acids from the receptor.…”
Section: Methodsmentioning
confidence: 99%
“…The recent cloning of the genes encoding the opioid receptors showed that they are members of the seven transmembrane G protein-coupled receptor family (22)(23)(24)(25)(26)(27)(28). There is about 60% amino acid identity among the sequences of the three subtypes , ␦, and .…”
mentioning
confidence: 99%